Seed priming and foliar application of Moringa oleifera leaf nano-extract enhance growth and chlorophyll in canola (Brassica napus) - SANAA NAWAR DHAHIR; MAHMOOD ALI SHAHER AL SHAHEEN (Asian Journal of Agriculture, 2025)
Abstract. Dhahir SN, Shaheen MASA. 2025. Seed priming and foliar application of Moringa oleifera leaf nano-extract enhance growth and chlorophyll in canola (Brassica napus). Asian J Agric 9: 433-441. Improving seed germination and physiological traits in crops like canola (Brassica napus) is crucial for enhancing yield and stress tolerance. Nanotechnology, particularly plant-based nano-extracts, offers eco-friendly alternatives for sustainable agriculture. This study evaluated the effects of seed priming and foliar spraying with varying concentrations of Moringa oleifera leaf nano-extract on germination and physiological performance of canola. A greenhouse experiment was conducted using a completely randomized design (CRD) with three nano-extract concentrations (5%, 10%, and 20%) and a distilled water control. The extract, synthesized via silver nitrate, was characterized by UV-Vis spectroscopy (peak at 435 nm), XRD, and SEM, confirming spherical nanoparticles (29-42 nm). Germination and physiological parameters were analyzed using ANOVA (p<0.05). Seed priming with 20% nano-extract significantly increased germination percentage by 53.3% (92% vs. 60%) and reduced mean germination time by 25% (122.4 vs. 163.2 hours). Root and shoot lengths increased by 60.0% (4.0 vs. 2.5 cm) and 57.9% (3.0 vs. 1.9 cm), respectively. Foliar spraying with 20% extract improved leaf area by 57.8% (82.6 vs. 52.3 cm²), root dry weight by 65.6% (1.62 vs. 0.98 g), and chlorophyll content by 54.6% (52.7 vs. 34.1 mg/g). Under greenhouse conditions, Moringa nano-extract—particularly at 20%—significantly enhanced germination and physiological traits in canola; however, field-based studies are required to validate these findings for broader agricultural applications. Although the findings demonstrate significant improvements under controlled greenhouse conditions, the absence of field trials and bulk control treatments is a limitation, and further field-based research is necessary to confirm broader agricultural applicability.